Acute Parastomal Hernia Presentations: A 10-Year Review of Management and Outcomes - Raziqah Ramli; Zi Qin Ng; Zi Qin Ng; Jason Diab; Jason Diab; Andrew Gilmore; Andrew Gilmore (Journal of Abdominal Wall Surgery)
IntroductionThe acute presentation of parastomal hernia (PSH) can range from exacerbation of pain to life-threatening incarceration. Managing the acute PSH is challenging, particularly in the presence of concomitant midline incisional hernia. Most literature focuses on the outcomes of elective PSH repair. There is a paucity of literature on optimal management approaches to emergency PSH presentations. We aim to evaluate the outcomes of management of acute PSH presentations at a large acute tertiary hospital over a 10-year-period.MethodsA retrospective analysis performed from May 2013 – May 2023 for all acute parastomal hernia presentations. The data collated included: demographics, index operation/pathology, duration of the stoma, clinical presentation, laboratory and imaging results and management outcomes (non-operative vs. operative intervention).ResultsTwenty-two admissions of acute PSH over the study period with the median age of 77 years, and 14 males. The median Charlson comorbidity score was 5. Most patients had stoma formation due to malignancy (12) with most end-colostomy (10). 11 patients had previous PSH repairs. 13 patients underwent operative intervention on index presentation via a combination of approaches. 4 required small bowel resection and 4 had resection of stoma; 4 had relocation of the stoma. There was one postoperative death due to sepsis related multi-organ failure. There were five recurrences of PSH on follow-up. Of the nine patients managed non-operatively, seven subsequently had elective reconstruction.ConclusionAcute PSH presentation usually requires operative intervention with considerable recurrence rates. The approach to the PSH repair, in the acute setting, needs to be individualised. Further study is required to assist with the development of guidelines for managing this difficult problem.